2023
DOI: 10.1101/2023.09.13.557639
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Default mode network spatio-temporal electrophysiological signature and causal role in creativity

E. Bartoli,
E. Devara,
H.Q. Dang
et al.

Abstract: The default mode network (DMN) is a widely distributed, intrinsic brain network thought to play a crucial role in internally-directed cognition. It subserves self-referential thinking, recollection of the past, mind wandering, and creativity. Knowledge about the electrophysiology underlying DMN activity is scarce, due to the difficulty to simultaneously record from multiple distant cortical areas with commonly-used techniques. The present study employs stereo-electroencephalography depth electrodes in 13 human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…First, the default-mode network (DMN) which mainly consists of the MPFC, posterior cingulate cortex, precuneus and temporoparietal junction, is involved in elaborative processing and self-generated thought, including mind-wandering, mental simulation, social cognition, autobiographical retrieval, and episodic future thinking – as supported by functional imaging ( 8 ). Interestingly, a recent series using stereo-electroencephalography in epilepsy patients showed that direct cortical stimulation at the level of several DMN hubs induced a decrease in creative thinking ( 9 ). Second, the executive fronto-parietal network (FPN) is also implied in creative cognition ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the default-mode network (DMN) which mainly consists of the MPFC, posterior cingulate cortex, precuneus and temporoparietal junction, is involved in elaborative processing and self-generated thought, including mind-wandering, mental simulation, social cognition, autobiographical retrieval, and episodic future thinking – as supported by functional imaging ( 8 ). Interestingly, a recent series using stereo-electroencephalography in epilepsy patients showed that direct cortical stimulation at the level of several DMN hubs induced a decrease in creative thinking ( 9 ). Second, the executive fronto-parietal network (FPN) is also implied in creative cognition ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%